PENINGKATAN KEMAMPUAN SISWA DALAM MEMBEDAKAN LINGKUNGAN SEHAT DAN TIDAK SEHAT DENGAN MENGGUNAKAN MEDIA GAMBAR PADA MATA PELAJARAN IPA DI KELAS I SDN 1 CIWANGI KECAMATAN LIMBANGAN - Een Sukaeni; Eros Rosita; Lilis Mulyani (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Science learning should be taught optimally to foster the ability to think, work and act scientifically and communicate it as an important aspect of life skills. Science learning in elementary schools should emphasize providing direct learning experiences through the use and development of process skills and scientific attitudes. The teacher as the spearhead in education is obliged to create a learning situation that can encourage students to have the courage to interact when learning is in progress. Therefore, teachers must be able to use all learning tools, especially in the use of relevant learning media to create a conducive learning situation. One of the aims of this study was to improve students' ability to distinguish between healthy and unhealthy environments in the science learning process for first grade students at SDN 1 Ciwangi Kec. Limbangan Garut Regency for the 2018/2019 Academic Year. The conclusion of this study is that the use of media images has a positive influence, which can increase students' learning motivation in science lessons as indicated by students' answers stating that students are interested and interested in active learning media so that they become motivated to learn.